2000
DOI: 10.1136/jnnp.68.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular decompression for trigeminal neuralgia: comments on a series of 250 cases, including 10 patients with multiple sclerosis

Abstract: Objective-To examine surgical findings and results of microvascular decompression (MVD) for trigeminal neuralgia (TN), including patients with multiple sclerosis, to bring new insight about the role of microvascular compression in the pathogenesis of the disorder and the role of MVD in its treatment. Methods-Between 1990 and 1998, 250 patients aVected by trigeminal neuralgia underwent MVD in the Department of Neurosurgery of the "Istituto Nazionale Neurologico C Besta" in Milan. Limiting the review to the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
125
0
14

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(155 citation statements)
references
References 42 publications
16
125
0
14
Order By: Relevance
“…The major complications reported by the authors included 2 postoperative deaths (0.2%), 1 brainstem infarction (0.1%), 4 intracerebral hematomas, 4 cerebellar edemas, 2 cases of hydrocephalus, 12 cases of facial palsy (2 permanent), 15 cases of extraocular muscle palsy (2 permanent), 16 cases of ipsilateral hearing loss, 22 cases of severe facial numbness, 20 cases of CSF leakage, 4 cases of pseudomeningocele, 5 cases of bacterial meningitis, 225 cases of chemical meningitis, 2 cases of pneumonia, and 1 case each of septicemia, myocardial infarction, transverse sinus thrombosis, pulmonary embolus, and permanent contralateral hearing loss. 1 Few other reports 2,24,47,48 used independent outcome assessments after MVD. 5 These case series confirm the results of Barker et al, with a 75% chance of maintaining pain relief at 3 years and a risk of operative mortality of 0.2% (rising to 0.5% in other reports).…”
Section: Discussionmentioning
confidence: 99%
“…The major complications reported by the authors included 2 postoperative deaths (0.2%), 1 brainstem infarction (0.1%), 4 intracerebral hematomas, 4 cerebellar edemas, 2 cases of hydrocephalus, 12 cases of facial palsy (2 permanent), 15 cases of extraocular muscle palsy (2 permanent), 16 cases of ipsilateral hearing loss, 22 cases of severe facial numbness, 20 cases of CSF leakage, 4 cases of pseudomeningocele, 5 cases of bacterial meningitis, 225 cases of chemical meningitis, 2 cases of pneumonia, and 1 case each of septicemia, myocardial infarction, transverse sinus thrombosis, pulmonary embolus, and permanent contralateral hearing loss. 1 Few other reports 2,24,47,48 used independent outcome assessments after MVD. 5 These case series confirm the results of Barker et al, with a 75% chance of maintaining pain relief at 3 years and a risk of operative mortality of 0.2% (rising to 0.5% in other reports).…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence in the literature to suggest increased major complication rates following MVD that are associated with increasing age. Previous studies have analyzed the results of MVD in elderly patients and demonstrated that the outcomes and morbidity rates are not related to age 2,5) . Broggi et al 5) , along with other physicians, consider MVD in the elderly to be easier and less time-consuming to accomplish than in younger patients, primarily due to brain atrophy and larger cisterns in the former, minimizing retractionrelated complications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have analyzed the results of MVD in elderly patients and demonstrated that the outcomes and morbidity rates are not related to age 2,5) . Broggi et al 5) , along with other physicians, consider MVD in the elderly to be easier and less time-consuming to accomplish than in younger patients, primarily due to brain atrophy and larger cisterns in the former, minimizing retractionrelated complications. The routine application of neurophysiological monitoring, including brainstem auditory evoked potential and facial electromyography, also helps to control the retraction.…”
Section: Discussionmentioning
confidence: 99%
“…24 Also, MVD, which was previously contraindicated in patients with MS, has returned as a surgical option after recent evidence indicating the possible coexistence of vascular compression of the REZ concomitant with the presence of a demyelinating plaque. 7,13,17,19 Recurrence of symptoms varies widely. In patients with MS, the rate and frequency of recurrence is higher than in the general population with TN, with a more frequent need for repeated treatments.…”
Section: 15mentioning
confidence: 99%